Desenvolvimento de sequestrante à base de ureia para dessulfurização de petróleo - Santos, Isis Gardênia Alves (2022)
The presence of sulfur compounds in crude oils is undesirable because, besides increasing the toxicity and impairing the quality of refined products, it generates combustion byproducts that impact the environment and are related to operational corrosion problems. To minimize these impacts, the removal of these compounds from crude oil can be accomplished by employing substances defined as scavengers. The objective of this work was to develop a sulfur compound scavengers for oil desulfurization, using urea as a basic species. The potential for reducing total sulfur content was performed from comparative tests of crude oil in contact and under stirring with aqueous urea solution and aqueous solution of β-D-glycosyl urea, synthesized and characterized in this work. A commercial MEA Triazine-based sequestrant was employed in comparing the desulfurization potential against the proposed sequestrants. Sulfur contents were determined by EDX, and suggest that urea in solution has sulfur compound removal potential of 209.59 mg g-1 urea. In equimolar relationship with the total sulfur present in the oil, β-D-glucosylurea has efficiency of 28.24 mg g-1 . The scavengers MEA Triazine had a lower efficiency of 8.40 mg g-1 . Molecular characterizations were performed by APPI(+)-FT Orbitrap MS of the crude oil before and after desulfurization to evaluate the effect of the treatment on chemical classes of sulfur-containing compounds. The crude oil desulfurized with urea showed the greatest reduction in the percentage of S1 and O3S1 class molecules. These results showed the possibility of reintroducing urea as a scavengers agent for sulfur compounds, adding value to a byproduct of the refining industry of low value and presenting an unprecedented application, with the potential to reduce the overall costs of the desulfurization process of the production units.